Differential effects of ambient or diminished CO2 and O2 levels on thylakoid membrane structure in light‐stressed plants. (March 2015) - Tsabari, Onie; Nevo, Reinat; Meir, Sagit; Carrillo, L. Ruby; Kramer, David M.; Reich, Ziv
Summary Over‐reduction of the photosynthetic electron transport chain may severely damage the photosynthetic apparatus as well as other constituents of the chloroplast and the cell. Here, we exposed Arabidopsis leaves to saturating light either under normal atmospheric conditions or under CO2‐ and O2‐limiting conditions, which greatly increase excitation and electron pressures by draining terminal electron acceptors. The two treatments were found to have very different, often opposing, effects on the structure of the thylakoid membranes, including the width of the granal lumenal compartment. Modulation of the latter is proposed to be related to movements of ions across the thylakoid membrane, which alter the relative osmolarity of the lumen and stroma and affect the partitioning of the proton motive force into its electrical and osmotic components. The resulting changes in thylakoid organization and lumenal width should facilitate the repair of photodamaged photosystem II complexes in response to light stress under ambient conditions, but are expected to inhibit the repair cycle when the light stress occurs concurrently with CO2 and O2 depletion. Under the latter conditions, the changes in thylakoid structure are predicted to complement other processes that restrict the flow of electrons into the high‐potential chain, thus moderating the production of deleterious reactive oxygen species at photosystem I.